2010
DOI: 10.1017/s0007114510004733
|View full text |Cite
|
Sign up to set email alerts
|

The influence of creatine supplementation on the cognitive functioning of vegetarians and omnivores

Abstract: Creatine when combined with P forms phosphocreatine that acts as a reserve of high-energy phosphate. Creatine is found mostly in meat, fish and other animal products, and the levels of muscle creatine are known to be lower in vegetarians. Creatine supplementation influences brain functioning as indicated by imaging studies and the measurement of oxygenated Hb. Given the key role played by creatine in the provision of energy, the influence of its supplementation on cognitive functioning was examined, contrastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
66
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 22 publications
1
66
1
5
Order By: Relevance
“…In the 4--object test, animals that had a higher concentration of GAA in the PFC spent This study demonstrated that there were no overt effects of either creatine or GAA supplementation on episodic--like memory in weaned pigs. This was contrary to our hypothesis given the dietary intake of creatine in these animals was thought to be low (Harris et al, 1997), and thus, like studies on vegetarians (Benton and Donohoe, 2011), we hypothesized that creatine supplementation would improve memory. Because episodic--like memory tests rely on hippocampal function (Kouwenberg et al, 2009), one possible explanation for this null result is that there were no observed effects of guanidino compound supplementation on creatine or GAA concentrations in the hippocampus.…”
Section: Correlationscontrasting
confidence: 77%
See 1 more Smart Citation
“…In the 4--object test, animals that had a higher concentration of GAA in the PFC spent This study demonstrated that there were no overt effects of either creatine or GAA supplementation on episodic--like memory in weaned pigs. This was contrary to our hypothesis given the dietary intake of creatine in these animals was thought to be low (Harris et al, 1997), and thus, like studies on vegetarians (Benton and Donohoe, 2011), we hypothesized that creatine supplementation would improve memory. Because episodic--like memory tests rely on hippocampal function (Kouwenberg et al, 2009), one possible explanation for this null result is that there were no observed effects of guanidino compound supplementation on creatine or GAA concentrations in the hippocampus.…”
Section: Correlationscontrasting
confidence: 77%
“…Creatine supplementation has been effective at enhancing cognitive ability during times of stress, such as during sleep--deprivation in younger (McMorris et al, 2006) and older adults (McMorris et al, 2007), as well as when endogenous creatine demand was enhanced (Benton and Donohoe, 2011;Rae et al, 2003). What can be hypothesized from those studies is that creatine supplementation enhances the capacity of the brain to convert ADP !…”
Section: Introductionmentioning
confidence: 99%
“…The study did not test for long-term effects but, as the authors note, short-term effects may be sufficient to assist with examination work, for instance, so short-term impacts may nevertheless lead to long-term gains in the labour market and in education. 15 Memory improvements were also found in a similar study, though only for vegetarians, not omnivores, and creatine supplementation had no impact on verbal fluency (Benton and Donohoe, 2011). Also double-blinded placebocontrolled tests for non-vegetarians have found positive connection between creatine supplementation and cognitive performance.…”
mentioning
confidence: 76%
“…Furthermore, Cr intake can also alleviate mental fatigue induced by stressor stimulus such as mathematical calculus (Watanabe et al 2002) and sleep deprivation (McMorris et al 2007b). A recent study showed that in vegetarians rather than in those who consume meat, Cr supplementation improves memory (Benton and Donohoe 2010). Moreover, both vegetarians and meat eaters experienced decreased variability in the responses to a choice reactiontime task (Benton and Donohoe 2010).…”
Section: Brain Disordersmentioning
confidence: 99%
“…A recent study showed that in vegetarians rather than in those who consume meat, Cr supplementation improves memory (Benton and Donohoe 2010). Moreover, both vegetarians and meat eaters experienced decreased variability in the responses to a choice reactiontime task (Benton and Donohoe 2010). The mechanisms underlying these findings remain to be elucidated.…”
Section: Brain Disordersmentioning
confidence: 99%